Crop rotation - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
Crop rotation is a critical agricultural practice employed to mitigate the adverse effects associated with monoculture systems. Monoculture, which refers to the cultivation of a single crop over a whole farm or area [1], has seen a constant spread worldwide since its early instances, such as the Caribbean sugarcane plantation in the 18th Century [2]. Among the many reasons concurring in the diffusion of monoculture, increased profitability through economies of scale is probably the main driver. Concentration on one crop allows for more efficient planting and harvesting, lower investment in diverse and costly equipment, reduced need for a workforce with specialized knowledge, and a comprehensive understanding of specific value chains and available markets